PANDANGAN KEPALA LINGKUNGAN PADA BANTUAN SOSIAL MASYARAKAT MISKIN DI LINGKUNGAN KELURAHAN TEMBUNG - Naura Rahmi Nadira Malau; Mhd. Fuad Zaini Siregar (Adiba Aisha Amira, 2023)
The aim of this research was to dig up information regarding the views of the head of the neighborhood in Tembung Subdistrict on the social assistance felt by the poor in his neighborhood. Social assistance aims to help reduce the burden of expenditure on poor people and also to overcome the problem of poverty itself. This study uses a qualitative knowledge method with a descriptive approach. The subject of this research is the head of the environment in Tembung Village. The research results show that there are several indicators of poverty that occur in society, one of which is the lack of employment opportunities which causes an increase in unemployment rates. With the existence of social assistance such as skills training, it is hoped that this will be a solution in overcoming the problem of unemployment in society. This research also highlights the benefits felt by poor communities who receive social assistance from the perspective of neighborhood heads. Therefore, this research highlights what causes poverty and unemployment in society as well as knowing the benefits received by poor people from the perspective of the head of the environment who observes the conditions of the people in their environment.